Integrating Gudeg in AI-Based Physics Learning Media: Feasibility Study on Enhancing Students' Critical Thinking, Creativity, and Physics Identity - Pujianto; Rofi Nur Hanifah; Bayu Setiaji; Riki Perdana; Taufiq Bayu Nur Rahmat; Devinda Putri Maharani; Syahid Ahmad Nashih (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop AI-based learning media integrated with Yogyakarta's local wisdom, particularly gudeg, in physics education. The research aims to facilitate 21st-century skills and students’ physics identity in the 5.0 era through socially and culturally relevant media. The research method used is Research and Development (R&D) with a 4D model, including define, design, and development stages. Observations and interviews were conducted at two high schools in Yogyakarta to identify learning needs. We developed three AI-based learning products: an e-book, an e-module, and an e-worksheet. Expert feasibility assessment showed very feasible results, with the e-book achieving the highest score (2.15), followed by the e-worksheet (2.05) and e-module (2.00). The use of these media increased students' interest, understanding, and skills in critical thinking, creativity, and physics identity. Integrating technology and local wisdom in physics learning media also positively contributes to education quality and supports Sustainable Development Goals (SDG 4: Quality Education, SDG 7: Affordable and Clean Energy, SDG 11: Sustainable Cities and Communities, and SDG 17: Partnerships for the Goals).